Enhancing perceived product value through peripheral product anecdotes. (16th December 2021) - Wiener, Hillary J.D.; Wiener, Joshua; Arnold, Todd
Abstract : Purpose: The purpose of this paper is to introduce a new strategic marketing tool: a peripheral product anecdote (PPA), or a brief, interesting story that is loosely connected to a product but not connected to its history, quality or usage. A PPA is contrasted with similar tools, such as product/brand heritage claims. This study investigates when PPAs are most effective at increasing willingness to pay. Design/methodology/approach: Five experiments examine the effect of different PPAs on willingness to pay. This study examines product-use situation as a moderator (Studies 3 and 4) and conversational value as a mediator (Studies 2 and 4). Findings: Customers will pay a premium for products with PPAs, but only when they intend to use the products in social situations where they could share the anecdote with others. Mediation analyses reveal these anecdotes are valuable because they provide purchasers with a conversation topic (a source of social currency). Practical implications: In contrast to brand heritage stories, nearly any firm can associate a PPA with their product. These anecdotes are a low-cost way for firms to increase willingness to pay for products. PPAs are innovative and varied, unlike brand heritage stories which tend to be static. Originality/value: This paper shows that customers sometimes want packaged goods, such as beer and snacks, to help them have conversations and will pay more for products that do so. It introduces the PPA as one way marketers can help customers achieve this goal of conversation.